Successful ecosystem-based management of Antarctic krill should address uncertainties in krill recruitment, behaviour and ecological adaptation - Bettina Meyer; Angus Atkinson; Kim S. Bernard; Andrew S. Brierley; Ryan Driscoll; Simeon L. Hill; Enrique Marschoff; Dale Maschette; Frances A. Perry; Christian S. Reiss; Emilce Rombolá; Geraint A. Tarling; et al. (Communications Earth & Environment, 2020)
Understanding of Antarctic krill must be at the heart of krill fishery management in order to protect the stock and its predators, according to a synthesis of krill ecology research.